Dealing of the Providers of Sport Media Content with Crises : (The Department of Media of the Ministry of Youth and Sports a Model) - Abdullah al-Ithawi, Hadi (ALBAHITH ALALAMI, 2012)
In a report by Transparency Organization in 2010, Iraq has 200 newspapers, magazines, sixty-seven radio stations and 45 satellite TV channels. The increase in these figures is measured in days or weeks and not months and years. This fact confirms the importance of studying content providers, especially youth sports content, for two reasons: the first is that young people constitute the highest percentage in Iraqi society, with all the potential involved in shaping the future aspects; the second reason is that for years sport has become an important pillar in people's lives not only in the entertainment aspect as it was seen in the past; Rather, sport has an influential presence in politics, economy and almost every detail of life.Accordingly, the study of sports content providers is an important study that derives its importance from the importance of the group to which the discourse is addressed. This leads us to study one of the main categories involved in the production of this discourse, namely the content providers of sports media.We have chosen the media department of the Ministry of Youth and Sports as a model because the department of media with the department office of the Iraqi National Olympic Committee are one of the tributaries the provide the content of Iraqi sports media. The Department of media in the ministry through its staff was able directly or indirectly to be a party in managing crises that hit the Iraqi sport in the years after the US occupation of Iraq in 2003.The aim of this study is to inform the job of this important segment in the field of sports media, which has become present in the lives of young people and others, whether through print press or through radio and television as well as websites.